Aspectos clínicos, anátomo-patológicos e evolutivos de uma série de lesões lobulares da mama tratadas em uma mesma instituição - Douglas Soltau Gomes (2010)
Purpose: To evaluate the frequency of lobular neoplasia (LN) in an institutional series of breast specimens, and to determinate possible associations among different subtypes of LN with low nuclear grade breast lesions (LNGBL). To describe clinical and histopathological characteristics of a series of cases of invasive lobular carcinoma (ILC) and which of these findings were associated to higher rate of local and/or systemic recurrence. Methods: This is a retrospective study, analyzing a series of cases of patients with pathological diagnosis of breast lobular lesions, treated at the Hospital das Clínicas, from August 1999 to December 2008. Clinical data were obtained from histopathological reports and medical records of patients. Cases of NL with original slides stained with hematoxylin and eosin available were reviewed and classified as atypical lobular hyperplasia (ALH), ductal involvement by cells of ALH (DIALH), lobular carcinoma in situ (LCIS) and pleomorphic LCIS. The coexistence of breast lesions such as columnar cell lesions (CCL), ductal hyperplasia, ductal carcinoma in situ (DCIS), invasive ductal carcinoma (NOS) and invasive lobular carcinoma (ILC) was evaluated. The association between NL and the different breast lesions were analyzed using the Fisher exact test. The disease-free survival (DFS) in months was evaluated in the ILC cases for the following variables: patients age, pathologic tumor size, number of axillary lymph node involved by metastases, stage, presence of associated lobular neoplasia, hormone receptor expression (estrogen and progesterone receptor), HER-2 expression, laterality (unilateral or bilateral), histologic tumor grade and type of surgery (radical or conservative). Survival curves were constructed using the Kaplan-Meier method and were compared using the log rank test. Results: During the study period, 5650 breast specimens were analyzed, 101 (1.8%) with LN and 91 cases (1.61%) showed ILC as primary diagnosis. From the 79 cases of LN that had slides available for review 78.5% presented had CCL, most then without atypia (67.7%). Florid/moderate or usual hyperplasia and atypical ductal hyperplasia were present in 40% and 10.1% respectively of cases of NL. LN was associated with DCIS in 21.5% of cases, and 64.7% of cases were high histologic grade DCIS. Invasive carcinoma was associated with LN in 45.6% of cases with similar frequency (47.2%) of invasive ductal carcinoma and invasive lobular carcinoma. When we assessed the ILC, we observed a higher frequency of LCIS (33.3%) in relation to ALH (2.8%). The average age of patients was 55.1 ± 12.9 years. The majority of patients was diagnosed by a palpable mass (62%), with an average size of 42.8 ± 22.2 mm (range 12-100 mm), and 42% of the cases were not seen on mammography. The majority of patients (57%) were diagnosed in initial stages (I and II). The most common type of surgical treatment was mastectomy (52%). Radiotherapy was performed in 55% of cases. Adjuvant chemotherapy and hormone therapy were performed in 42% and 59% of cases respectively. Tumor size greater than 2 cm (p = 0.03), the presence of metastases in axillary lymph nodes and the number of lymph nodes affected (p = 0.001) were strongly related to DFS. Conclusions: Our findings suggest a strong association between lobular neoplasia and columnar cell lesions without atypia. We also observed a higher frequency of invasive carcinoma, especially ILC, associated with LCIS when compared to ALH. Patients with ILC with tumors larger than 2 cm and presence of lymph axillary lymph node metastases showed lower DFS.